Lesekiste Mit übergangsstufe (Reading Box) In German Language Learning - Aini, Desti Nur (KnE Social Sciences, 2017)
Reading activities in learning German as a foreign language are not simply done during the teaching and learning process. In European standard curriculum (GER= Germanische Europäische Referenzrahmen), reading constitutes one of the language test items. Reading in German as a foreign language is suggested to improve students’ competence in German. Beyond that, reading also leads to the improvement of knowledge related to German culture. In order to level up and optimize the interest of high school students to learn German language, one of the strategies that can be carried out is Lesekiste mit Übergangsstufe or reading box. This box provides some texts for the students. These texts are stacked based on difficulty levels, starting from the easy towards the intermediate, and complex ones. In this activity, the students have equal access to all the texts available in the box. Furthermore, students can be asked to retell the text through “Darstellungsformen” (retelling technique) by using mind map, charts, or sketch (Skizze). This activity is designed to achieve the improvement of teacher’s competence for the sake of the teachers themselves and for the students’ learning development. Keywords: Reading activity, German as a foreign language, Lesekiste mit Übergangsstufe